The Masculine Mystique: Franco La Cecla’s and Robert Bly’s Concepts of Man - Żukowska, Kamila (Hybris, 2018)
The object of the paper is to present the two concepts of masculinity worked on the ground of the so-called male studies. The peculiar and distinctive feature of these theories, formulated by Franco La Cecla and Robert Blye, is that they give up the traditional conceptual background of feminism so as to replace it with a newly developed methodology. Moreover, both authors pay their attention to the masculine version of the historical “problem with no name”, resulting in this case from the bias of feminism against men. The main aim of the paper is to provide a critical analysis of the mentioned concepts.